The Unitive Power of the Hug: Franciscan-Dominican Reciprocity in Geroglífico Sagrado by Alonso de Hita - Taiano, Leonor (Teología, 2023)
In this paper I analyse Geroglífico Sagrado de la amistad más verdadera y vivo traslado de la divina y celestial en los gloriosos patriarcas Sancto Domingo y San Francisco (1692) by Alonso de Hita. My research explores how the allusions to the hug between St Francis of Assisi and Saint Dominic de Guzmán serve to promote the importance of the Franciscan and Dominican communities. As a result, I mention the relevance of the pair predication-caritas has in the book, I enquire how the hug represents the theological evolution of the members of the L’Ordine dei Frati Minori and La Orden de predicadores. In addition, I examine the foundation of the Franciscan-Dominican covenant of friendship. Finally, I mention the motifs that make of St Francis and St Dominic the prototypes of the good Christian.